2000
DOI: 10.2514/2.2692
|View full text |Cite
|
Sign up to set email alerts
|

Flow Complexities of Slender Wing Rock

Abstract: IntroductionM ILITARY design trends toward the use of unmanned, nless aircraft 1 have renewed interest in the unsteady aerodynamics of slender wing rock. One important aspect of the problem of wing rock control is the potential impact of typical con gurational details on delta-wing aircraft, such as the presence of a centerbody. Early experimental results for a sharp-edged 80-deg delta wing indicated that breakdown of the leading-edgevortices played a role 2,3 ( Fig. 1). It could be shown that rather than bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…For the oscillations appearing on the wing-body configurations, early research state that the main cause to the asymmetric vortices appearing in the forebody. Wind-tunnel experimental data provided by Ericsson [3,4] showed that the wing also has a large effect on the wing oscillations at small and medium attack angles. Han [5] used numerical methods to investigate the rock characteristics of the wing-body assembly and obtained a more specific flow field structure than the experiments.…”
Section: Introductionmentioning
confidence: 99%
“…For the oscillations appearing on the wing-body configurations, early research state that the main cause to the asymmetric vortices appearing in the forebody. Wind-tunnel experimental data provided by Ericsson [3,4] showed that the wing also has a large effect on the wing oscillations at small and medium attack angles. Han [5] used numerical methods to investigate the rock characteristics of the wing-body assembly and obtained a more specific flow field structure than the experiments.…”
Section: Introductionmentioning
confidence: 99%